Design of Arrayed Waveguide Grating (AWG) for DWDM/CWDM applications based on BCB polymer - Adam, Ismahayati; Ibrahim, Mohd. Haniff; Mohd. Kassim, Norazan; Mohammad, Abu Bakar; Mohd. Supa’at, Abu Sahmah (Faculty of Electrical Engineering, 2008)
Conventional AWG structures based on BenzoCyclobutene (BCB 4024-40) polymer for DWDM/CWDM application are proposed. AWGs are designed on silica substrate with the polymer waveguide refractive index of 1.5556 and layer refractive index of 1.537. An objective of this system is to multiply an optical fiber’s transmission capacity by sending signals simultaneously at multiple wavelengths over a single fiber. Two types of four channels AWG have been successfully designed and operate well in 1550 nm communication window at their desired frequency spacing. Although numbers of AWG structure have been designed and implemented, this work is considered to be the first that based on BCB polymer